2006
DOI: 10.1111/j.0014-3820.2006.tb01835.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Female Mating Preferences: Differentiation From Species With Promiscuous Males Can Promote Speciation

Abstract: Abstract. Females of many species are frequently courted by promiscuous males of their own and other closely related species. Such mating interactions may impose strong selection on female mating preferences to favor trait values in conspecific males that allow females to discriminate them from their heterospecific rivals. We explore the consequences of such selection in models of the evolution of female mating preferences when females must interact with heterospecific males from which they are completely post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 100 publications
(73 reference statements)
3
99
0
Order By: Relevance
“…We also found that females from mixed-and pure-species populations express divergent preferences for conspecific male call characters. These divergent preferences are likely to be the result of reinforcement, because the evolution of enhanced discrimination of conspecifics from heterospecifics will often concomitantly affect patterns of mate choice among conspecifics [1,8,10,22,57]. That mixed-and pure-species populations exhibit such divergent preferences is significant, because it indicates that female preferences can become locally adapted to the presence of heterospecifics, even at a relatively fine spatial scale.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also found that females from mixed-and pure-species populations express divergent preferences for conspecific male call characters. These divergent preferences are likely to be the result of reinforcement, because the evolution of enhanced discrimination of conspecifics from heterospecifics will often concomitantly affect patterns of mate choice among conspecifics [1,8,10,22,57]. That mixed-and pure-species populations exhibit such divergent preferences is significant, because it indicates that female preferences can become locally adapted to the presence of heterospecifics, even at a relatively fine spatial scale.…”
Section: Discussionmentioning
confidence: 99%
“…When interactions with heterospecifics are costly (as when hybridization results in offspring of low fitness), selection should favour behaviours that prevent reproductive interactions, thereby enhancing isolation between species (or incipient species) to the point where gene exchange between them is reduced or completely eliminated [3,36,38,39]. Yet reinforcement (and, more generally, reproductive character displacement) may also serve to initiate divergence-and possibly speciation [1,2,[6][7][8][9][10][11][12][13][14][15][16][17]43]. Indeed, if reinforcement occurs with different heterospecifics in different parts of a focal species's range, or in different ways across sympatry and allopatry, it can contribute to 'speciation cascades' in which multiple speciation events are triggered by reinforcement [1,8,13], a process that has also been called the 'cascade reinforcement hypothesis' and 'RCD speciation' [9,15,16,20] (see also [6]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These features of the ecology and natural history of demoiselles make them excellent study organisms to investigate how sex differences in developmental plasticity and learning might affect local adaptation and population divergence in the presence or absence of conspecifics and in the face of gene flow. As these demoiselles and other odonates (dragonflies and damselflies) often show weak ecological differentiation between species [25,26], they challenge models of ecological speciation and point to non-ecological speciation mechanisms through social selection, sexual selection, sexual conflict and/or learning [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%